ON PREHISPANIC OCCUPATIONS IN THE LOW BASIN OF THE NEGROMAYO RIVER (LUCANAS-AYACUCHO): AN APPROACH FROM THE ARCHAEOLOGICAL SITE OF CANICHI - Cámara Guerrero, Jorge (2009)
This report has been made since a superficial recognition at Canichi, an archeological settlement located on the left bank of Negromayo River, Lucanas Province, Ayacucho Department. Based on archaeological evidences and with the use of ethnohistorical references, in a complementary way, both chronological position and the nature of belated period activities will be discussed in the following report, emphasizing the role that Canichi could have played along the lower basin throughout the Late Intermediate Period and changes and continuities in the social organization of local residents during the process of conquest and consolidation of the Inka State in the region.